A new recessive syndrome of unusual facies and multiple structural abnormalities. Issue 9 (September 1991) - Thakker, Y; Donnai, D
Abstract : Two sibs with a similar pattern of dysmorphic facial features and multiple structural abnormalities are reported. Both had a normal karyotype. The parents are first cousins and neither shows any stigmata of the disorder. In view of the consanguinity and pattern of malformations, autosomal recessive inheritance seems likely.